Noxious weed survey of the Pueblo Chemical Depot 2015 - Smith, Pamela, author; Greenwell, Amy Lavender, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2016)
Nine species of state listed noxious weeds were mapped at PCD in 2015 and assessed for their threat level based on coverage, plant biology, surrounding land use and their potential to spread. The use of repeatable data is important to facilitate comparisons of weed populations over time. This report and the spatial dataset will provide a useful tool to develop weed mitigation strategies and invasive species control plans to comply with noxious weed regulations.
Keywords: botany; inventories/biological surveys; invasive species